Systematic Risk, Earnings Persistence, and Earnings Response Coefficient: Moderator and Mediator Analysis (Evidence from Emerging Market Indonesia) - Verdanica Desta Purwa; Zaki Fakhroni; Yunita Fitria (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
The results showed that systematic risk negatively and significantly affected the earnings response coefficient. Earnings persistence and investment opportunity set positively and significantly affected the earnings response coefficient. Both systematic risk and earnings persistence positively and significantly affected the investment opportunity set. The investment opportunity set did not mediate the relationship between systematic risk, earnings persistence, and the earnings response coefficient. However, audit quality moderated the effect of systematic risk and earnings persistence on the earnings response coefficient